2014
DOI: 10.1144/sp400.30
|View full text |Cite
|
Sign up to set email alerts
|

Excavation-induced fractures network surrounding tunnel: properties and evolution under loading

Abstract: The investigation of the induced fractures network around seals in drifts or shafts, and in particular its evolution, is a key issue for the performance assessment of an underground waste repository. Within this framework, a specific experiment was designed and implemented in the Meuse/Haute-Marne Underground Research Laboratory (URL). This experiment, called CDZ (Compression of the Damaged Zone), is dedicated to studying the effect of mechanical compression within the induced fractures zone of the Callovo-Oxf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Observation boreholes can be assigned at favorable locations to develop a model of the fracture network by extrapolating the observed fractures in single boreholes. Figure 12 shows an example of the observation of excavation-induced fractures around a circular tunnel in claystone conducted at the Meuse/Haute-Marne Underground Research Laboratory 10 Geofluids [94]. Similarly, several observations can be designed according to the retreating process of the longwall face to determine the evolution of the fracture network.…”
Section: Outstanding Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observation boreholes can be assigned at favorable locations to develop a model of the fracture network by extrapolating the observed fractures in single boreholes. Figure 12 shows an example of the observation of excavation-induced fractures around a circular tunnel in claystone conducted at the Meuse/Haute-Marne Underground Research Laboratory 10 Geofluids [94]. Similarly, several observations can be designed according to the retreating process of the longwall face to determine the evolution of the fracture network.…”
Section: Outstanding Issuesmentioning
confidence: 99%
“…Only a few works have studied the density distribution [2,99], mainly because there is no demand for a detailed fracture profile of the pillar in most longwall activities. It is believed the fracture profile can be roughly determined using the method presented in [94]; however, additional difficulties could arise as the longwall face approaches the target site since the fractures develop rapidly and produce complex networks. Detailed fracture observations in the longwall face are not available because of the continuous operation of longwall mining.…”
Section: Outstanding Issuesmentioning
confidence: 99%
“…They showed that microfractures extend beyond the fractured zone surrounding the excavation on the bases of hydraulic conductivity results. De La Vaissière et al (2014) studied the effect of mechanical compression within the EDZ through the Compression of the Damaged Zone (CDZ) experiment, and observed self-sealing processes. Zhang (2011) also investigated the selfsealing of fractures in argillites by testing samples through a similar experimental approach, and found strong evidence for complete self-sealing within the time period of months to years.…”
Section: Edz Characterizationmentioning
confidence: 99%
“…The low-values zone is associated with the presence of groups of fractures (Damaj, 2006 Les principaux travaux utilisant des méthodes sismiques de « puits à puits » sont résumés dans le Tableau 3 dans lequel les forces et les faiblesses de chaque étude sont présentées. Ce tableau permet de constater que la méthodologie a su évoluer rapidement avec des techniques utilisées pour une caractérisation « statique » de la zone endommagée (Nicollin et al, 2008) vers des approches permettant un suivi temporel (Manukyan et al, 2012 ;La Vaissière et al, 2014) et des représentations quasi 3D de la zone endommagée (Balland et al, 2013) (Fig. 8).…”
Section: Méthodes Sismiques « Puits à Puits »unclassified